Outcome of Minimal Invasive Lateral Buttressing in Proximal Metaphyseal-Articular Tibial Fractures - 2RAZA ELAHIRANA TANVIR AFZAL MUHAMMA, MUHAMMAD HANIF (Journal of Fatima Jinnah Medical University, 2018)
Background: Management of comminuted bicondylartibial plateau fractures remains a difficult task for the surgeons and mode of treatment is controversial. Open reduction and internal fixation may result in major wound problems. Our study evaluated the functional outcome of minimally invasive plating in high energy tibial plateau fractures. Materials and Methods: 31 patients having Schatzker type V and VI were treated with minimally invasive technique and were followed up in outpatient department. Radiographs were obtained and functional outcome was determined by the Oxford Knee Score criteria. Results: Patients were followed up to 20th postoperative week and at the end of the final follow up radiographic union was seen in all patients. Oxford Knee Score was excellent in 21 patients, good in 7 patients and moderate in 3 patients. The patients in moderate category were those which had fasciotomy done for compartment syndrome following injury. No complication regarding soft tissue was seen. Conclusions: Minimal Invasive Percutaneous Plate Osteosynthesis produces excellent radiological and functional outcome in proximal tibial fractures